Flattening of the Phillips Curve : Implications for Monetary Policy - Iakova, Dora (IMF Working Papers; Working Paper ;, 2007)
Over the past decade, inflation has become less responsive to domestic demand pressures in many industrial countries. This development has been attributed, in part, to globalization forces. A small macroeconomic model, estimated on UK data using Bayesian estimation, is used to analyze the monetary policy implications of this structural change. The focus is on the implications of a globalization-related flattening of the Phillips curve for the trade-off between inflation and output gap variability and for the efficient monetary policy response rule.